Structural analysis of the northeastern Mohns Ridge - Svendsen, Tor Erik (The University of Bergen, 2009)
A structural analysis of the northeastern Mohns Ridge situated in the Norwegian-Greenland Sea has been conducted using bathymetric data acquired during surveys in 2000 and 2001. Fault pattern and volcanic features are interpreted from this bathymetry as well as dip, length and displacement. These measurements have further been used to produce fault maps, profiles and models. The study area comprises the oblique spreading northern Mohns Ridge, the orthogonal spreading Mohns-Knipovich Ridge Bend and the southernmost highly oblique spreading Knipovich Ridge. Spreading rates lie between the slow- and ultraslow class of spreading ridges and the ridge is characterized by a deep rift valley. Observations and interpretations of relay structures illustrate how faults link together and grow in both horizontal and vertical direction. Maximum displacement-length relation of the study area conforms to maximum displacement-length data from continental rift settings and other fault populations in spite of differences in crustal thickness and rheology. The study area has been subdivided at segment scale. Area 1 is situated in between two axial volcanic ridges (AVRs) and area 2 has an AVR directly adjacent in the rift valley. Area 1 is characterized by rather symmetric fault geometry and in profile the faults are equally spaced and show a slight decrease in dip as distance off-axis increases. In contrast area 2 is characterized by great variations in topographic expression. It is characterized by several outward facing low-angle detachment faults with varying degrees of displacement as well as basins situated off-axis in relation to the detachment fault. These outwards facing faults have previously been interpreted to represent core complexes based on petrologic data although they are not structurally confined. Analysis has better confined these structures and their characteristics and proposed evolutionary models are presented. It is further suggested that several evolutionary stages of core complex formation is present in area ...